SIFAT FISIKOKIMIA BERONDONG HANJELI (Coix lacryma-jobi L) - Kun Tanti Dewandari; Joni Munarso; Rahmawati Rahmawati (Jurnal Penelitian Pascapanen Pertanian, 2020)
Hanjeli adalah salah satu tanaman potensial untuk diversifikasi pangan. Karbohidrat dan pati dalam biji hanjeli mirip dengan sereal lainnya seperti gandum, sorgum, jagung. Produk olahan sereal salah satunya adalah berondong yang diperoleh dengan metode puffing. Puffing adalah proses pengolahan pangan yang menyebabkan perubahan struktur sehingga terjadi penggembungan atau perluasan volume akibat pengaruh suhu dan tekanan. Pada penelitian ini dilakukan proses puffing pada biji hanjeli menggunakan microwave dengan perlakuan A (Tingkat Energi) dan B (Waktu proses) dengan 3 kali ulangan. Hasil penelitian menunjukkan bahwa energi gelombang mikro yang digunakan dalam proses pengujian popping hanjeli memiliki dampak nyata dengan nilai signifikan <0,05 terhadap kadar air, lemak, karbohidrat. pengujian konten dan organoleptik pada parameter warna dan tekstur dengan tingkat energi sedang. Perlakuan terbaik yang dilakukan pada penelitian ini merupakan produk berondong hanjeli dengan tingkat energi medium dan waktu proses 2,5 menit. Berondong hanjeli tersebut memiliki hasil analisa fisik pada densitas kamba 0,30 %. Berondong hanjeli memiliki hasil analisa kimia pada kadar air 3,59%, kadar abu 0,13%, kadar protein 14,60%, kadar lemak 1,14%, kadar karbohidrat 80,54%, kadar amilosa 11,09%, kadar amilopektin 60,22%. Physicochemical Properties Of Popping Hanjeli (Coix Lacryma-Jobi L)Utilitization of Hanjeli plant has not been done yet because of society’s lack of knowledge. The carbohydrate and starch in Hanjeli seeds are similar to other cereals’ content such as wheat, sorghum, corn and barley. The brunch cereal is the result of puffing process. In this research, the puffing process was done by using the microwave. One of the benefits of this research is to ascertain of puffing process by using the microwave towards Hanjeli seeds. This research used the experimental method with two factors of Completely Randomized Factorial Design (CRFD) which consists of factor A (Power Level) and factor B (Time process) with three times repetition. Analytical techniques that were used were variance or Analysis of Variance (ANOVA) and continued to Post-Hoc Test with Tukey’s test method. Analysis of physical properties which was conducted is bulk density. Analysis of chemical properties which was conducted are water, ash, protein, fat, carbohydrate, amylose and amylopectin. Organoleptic analysis which was conducted are acceptance test (hedonic) and hedonic quality test. Based on the research result of change in the physicochemical properties, the microwave energy which was used in the puffing process to test the popping hanjeli has the real impact with a significant value < α (0.05) towards the popping hanjeli’s quality on the tests of water, fat, carbohydrate content and organoleptic testing on color and texture parameters with medium energy levels. Time usage of popping hanjeli using the microwave has the real impact with a significant value < α (0.05) towards the popping hanjeli’s quality on the tests of water, fat, carbohydrate content and organoleptic testing on color and texture parameters with medium energy level. There is a different interaction between the energy level and time process, it has the real impact with a significant value < α (0.05) towards the popping hanjeli’s quality which at the medium energy level with a time process of 2,5 minutes.